2016
DOI: 10.1016/j.trac.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes and graphene nano field-effect transistor-based biosensors

Abstract: Please cite this article as: Thien-Toan Tran, Ashok Mulchandani, Carbon nanotubes and graphene nano field-effect transistor-based biosensors, Trends in Analytical Chemistry (2016), http://dx.doi.org/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 80 publications
1
85
0
1
Order By: Relevance
“…The TG configuration is also known as liquid gating or electrolyte gating. 11,17,93 Generally, in bottom-gate configuration, S, D and channel are fabricated on the top on SiO 2 /Si substrate where SiO 2 layer act like an insulator between graphene and heavily-doped Si (typically, p…”
Section: Graphene Based Fet Biosensing Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The TG configuration is also known as liquid gating or electrolyte gating. 11,17,93 Generally, in bottom-gate configuration, S, D and channel are fabricated on the top on SiO 2 /Si substrate where SiO 2 layer act like an insulator between graphene and heavily-doped Si (typically, p…”
Section: Graphene Based Fet Biosensing Systemmentioning
confidence: 99%
“…6,7 Among these nanomaterials, metallic nanomaterials, silica nanoparticles (NPs), dendrimers, quantum dots (QDs), polymer NPs, carbon nanotubes (CNTs), nanodiamonds (NDs), and 2D-nanomaterials [graphene, hexagonalboron nitride (h-BN), transition metal dichalcogenides (TMDs) such as niobium selenide (NbSe 2 ), molybdenum disulfide (MoS 2 ), and tungsten disulfide (WS 2 )] are highly studied and have significantly contribution to biosensor development. [8][9][10][11][12] In particular, graphene is the most promising nanostructured carbon material that is used in the bioanalytical area and has stimulated intense research as it possesses an excellent combination of enhanced specific surface area, electrical conductivity, chemical stability, ease of manipulation and biocompatibility, thus, providing more specific sites to capture foreign moieties with high sensitivity. In addition, it is resistant to the harsh ionic solutions found in body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence-based techniques (total internal reflection fluorescence microscope, confocal microscopy and fluorescence correlation spectroscopy), opposed or combined to force-based techniques (optical trap, magnetic trap and atomic force microscope) (1)(2)(3)(4), offer the possibility to study molecules one at a time and to highlight reaction pathways and reaction intermediates that ensemble methods tend to hide because of their effect of averaging (5). More recently, another approach has been emerging based on single-molecule field-effect transistors (smFETs), in which an individual molecule is immobilized on a nanoscale electrical circuit, such as a carbon nanotube (6)(7)(8)(9)(10)(11)(12) or silicon nanowire (13)(14)(15)(16). By recording fluctuations in the electrical conductance of such circuits, studies have reported the realtime monitoring of transitions between different conformational states, such as hybridization (17)(18)(19)(20), folding events in nucleic acids (17,21), enzymatic catalysis with a ultra-high sensitivity and specificity (22,23), and also other applications in biology and medicine, such as imaging (24,25) and drug delivery (26,27) to cancer and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is an allotrope of carbon which is made up of monolayer of sp2 bonded carbon atoms arranged in honeycomb lattice (Tran & Mulchandani 2016;Wang et al 2015). The carbon-carbon (C-C) bond is the basic bonding in graphene, with bond length of approximately 0.142 nm (Yan et al 2014).…”
Section: Introductionmentioning
confidence: 99%